2022
DOI: 10.1111/apha.13849
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of heart rate following genetic deletion of the ß1 adrenergic receptor in larval zebrafish

Abstract: Aim Although zebrafish are gaining popularity as biomedical models of cardiovascular disease, our understanding of their cardiac control mechanisms is fragmentary. Our goal was to clarify the controversial role of the ß1‐adrenergic receptor (AR) in the regulation of heart rate in zebrafish. Methods CRISPR‐Cas9 was used to delete the adrb1 gene in zebrafish allowing us to generate a stable adrb1−/− line. Larval heart rates were measured during pharmacological protocols and with exposure to hypercapnia. Expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…In the studied vertebrates, HR and its adjustment to physical exercise show notable differences and could be influenced by several intrinsic factors, such as age (as has already been evidenced in humans) [65,[84][85][86][87][88][89]. As illustrated in Table 1, fish, amphibians, and reptiles show a limited range of HR.…”
Section: Adjustment Of the Hr To Exercise In Vertebratesmentioning
confidence: 78%
See 1 more Smart Citation

Cardiovascular Response to Exercise in Vertebrates: Update

López-Román,
Gómez-Lucas,
Jiménez-Herranz
et al. 2024
Preprint
“…In the studied vertebrates, HR and its adjustment to physical exercise show notable differences and could be influenced by several intrinsic factors, such as age (as has already been evidenced in humans) [65,[84][85][86][87][88][89]. As illustrated in Table 1, fish, amphibians, and reptiles show a limited range of HR.…”
Section: Adjustment Of the Hr To Exercise In Vertebratesmentioning
confidence: 78%
“…HR in vertebrates is determined by the activity of the heart pacemaker and various factors, such us temperature, acetylcholine, adrenaline, or calcium, that modulate its electrical activity via nervous and hormonal pathways [64][65][66][67][68]. SV is determined by contractility and the characteristics of the ventricle, mainly regarding its filling capacity.…”
mentioning
confidence: 99%

Cardiovascular Response to Exercise in Vertebrates: Update

López-Román,
Gómez-Lucas,
Jiménez-Herranz
et al. 2024
Preprint
“…However, it appears plausible that loss of adrb1 might not have been sustainable without the expansion of adrb2 and adrb3 repertoires. By analogy, knockout of adrb1 in zebrafish leads to increased cardiac expression of adrb2b and adrb3b genes (Joyce et al, 2022). As such, this study contributes to the growing appreciation of the redundancy between adrb paralogs, particularly in teleosts.…”
Section: Resultsmentioning
confidence: 99%
“…In mice, deletion of Adrb1 results in high prenatal mortality and renders the heart insensitive to ß-adrenergic stimulation (Rohrer et al, 1996). In zebrafish, by contrast, adrb1 knockout has no obvious adverse effects on viability and fertility, at least when raised in optimized aquaculture conditions (Joyce et al, 2022), although it is not known if the knockout fish would survive under natural conditions. Routine heart rate is suppressed in adrb1 knockout larval zebrafish, although they are still able to respond to ß-adrenergic stimulation with tachycardia, presumably mediated by other ß-ARs (Joyce et al, 2022).…”
Section: Evolutionary Implications and Conclusionmentioning
confidence: 99%
“…Zebrafish and medaka have recently been established as model animals of human diseases [24][25][26][27]. Several pharmacological studies have revealed that larval-stage zebrafish express receptors for sympathetic and parasympathetic neural transmission are expressed in zebrafish larvae and that heart rates in zebrafish larvae change in response to both sympathetic and parasympathetic input with or without anesthesia [17,21,[28][29][30], although one of these studies further demonstrated that the autonomic components of the reflex are poorly developed in 5-days-old larvae of zebrafish, suggesting that ANS function is incompletely developed at this stage [21]. Moreover, to evaluate long-term changes in ANS activity such as those induced by environmental changes, it is necessary to study adult animals to avoid major alterations in ANS activity during embryonic development, growth or sexual maturation.…”
Section: Introductionmentioning
confidence: 99%